2020
DOI: 10.1016/j.radonc.2020.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Defining oligometastatic disease from a radiation oncology perspective: An ESTRO-ASTRO consensus document

Abstract: Background: Recognizing the rapidly increasing interest and evidence in using metastasis-directed radiotherapy (MDRT) for oligometastatic disease (OMD), ESTRO and ASTRO convened a committee to establish consensus regarding definitions of OMD and define gaps in current evidence. Methods: A systematic literature review focused on curative intent MDRT was performed in Medline, Embase and Cochrane. Subsequent consensus opinion, using a Delphi process, highlighted the current state of evidence and the limitations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
278
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 420 publications
(331 citation statements)
references
References 109 publications
4
278
1
2
Order By: Relevance
“…Some patients in our study had oligometastatic disease not exceeding two extrathoracic metastases. It has been shown that patients with limited metastatic disease benefit from (chemo)radiotherapy of the primary tumor in combination with metastasis-directed local treatment with regard to PFS and OS [27][28][29][30][31]. In our cohort we observed a median PFS of 7.0 months and a median OS of 19.6 months for the subgroup of UICC stage 4 patients.…”
mentioning
confidence: 48%
“…Some patients in our study had oligometastatic disease not exceeding two extrathoracic metastases. It has been shown that patients with limited metastatic disease benefit from (chemo)radiotherapy of the primary tumor in combination with metastasis-directed local treatment with regard to PFS and OS [27][28][29][30][31]. In our cohort we observed a median PFS of 7.0 months and a median OS of 19.6 months for the subgroup of UICC stage 4 patients.…”
mentioning
confidence: 48%
“…Over the past year, growing efforts have been undertaken to define oligometastatic disease and its different states in order to standardize reporting thereof (20,21). As a result, the following two conditions must be met: the maximum number of five metastases should not be surpassed, and all of them must be safely treatable, whereas a controlled primary is optional (21). According to the timing of its appearance, several distinct clinical presentations, discussed further in the text, are recognized (20)(21)(22).…”
Section: Approach To Oligometastatic Diseasementioning
confidence: 99%
“…As a result, the following two conditions must be met: the maximum number of five metastases should not be surpassed, and all of them must be safely treatable, whereas a controlled primary is optional (21). According to the timing of its appearance, several distinct clinical presentations, discussed further in the text, are recognized (20)(21)(22). Since a standard approach has not been determined in these situations, all patients who could potentially be considered for a local approach should be discussed in multidisciplinary tumor boards.…”
Section: Approach To Oligometastatic Diseasementioning
confidence: 99%
“…Metastasized NSCLC patients with oligo-metastatic disease showed a benefit in progression free survival (PFS) when local ablative therapy was added to systemic therapy (chemotherapy ( [6][7][8]) or tyrosine kinase inhibitor ( [7,8])); one trial also demonstrated an improved overall survival (OS) [7]. Oligometastatic disease is usually defined as "limited metastasis" (NCCN guideline [9]), up to three metastases (ESMO guideline [5]) or up to five metastases (European Organization for the Research and Treatment of Cancer (EORTC) lung cancer group consensus definition [10][11][12] and most clinical trials [13][14][15]). These guidelines advise to treat these patients with a combination of systemic therapy and local ablative therapy, preferably within a clinical trial.…”
Section: Introductionmentioning
confidence: 99%